2020
DOI: 10.1021/acs.molpharmaceut.9b01213
|View full text |Cite
|
Sign up to set email alerts
|

Brain Angiogenesis Induced by Nonviral Gene Therapy with Potential Therapeutic Benefits for Central Nervous System Diseases

Abstract: Brain angiogenesis induced by non-viral gene therapy vectoring VEGF with potential therapeutic benefits for central nervous system diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Hence, formulation 1, which contains chloroquine in the aqueous phase and surfactants incorporated in the organic phase, might be an encouraging non-viral strategy for gene therapy aimed at cystic fibrosis disease. In this regard, previous in vivo studies carried out by our group showed a successful gene delivery capacity of formulation 1 in central nervous system [62], but an in depth biophysical study and implementation in congenital disease model, as cystic fibrosis, was a missing issue.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, formulation 1, which contains chloroquine in the aqueous phase and surfactants incorporated in the organic phase, might be an encouraging non-viral strategy for gene therapy aimed at cystic fibrosis disease. In this regard, previous in vivo studies carried out by our group showed a successful gene delivery capacity of formulation 1 in central nervous system [62], but an in depth biophysical study and implementation in congenital disease model, as cystic fibrosis, was a missing issue.…”
Section: Discussionmentioning
confidence: 97%
“…As "helper" component, formulations 1 and 2 included chloroquine due to its capacity to protect and interact with the DNA [60,61]. Moreover, chloroquine improves the endosomal escape impairing the fusion of endosomes and lysosomes because of its protonation inside the vesicles, causing a higher pH value that avoids the enzymatic lysosomal activity [30,[62][63][64][65]. Therefore, in the present work, we hypothesized that chloroquine would not only act as a "helper" component, but also as a biophysical performance enhancer agent inside the niosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Intracranial injection of nucleic acids complexes was one of the first approaches to bypassing the BBB. Intracortical injection in mice of pVEGF-GFP complexed with cationic lipid showed angiogenesis in the regions surrounding the injection/transfection sites [53]. This approach has also been used for the transfection of RNAi.…”
Section: Dna/rna Transfection Into the Central Nervous Systemmentioning
confidence: 96%
“…Among lipid nanoparticles, niosomes have been employed for in situ gene therapy purposes in CNS (Al Qtaish et al, 2020). Interestingly, brain angiogenesis has been achieved in vivo by the intracerebral administration of niosomes vectoring the Vegf 165 gene at the cortex level (Gallego et al, 2020) (Table 2). In this work, niosomes were able to efficiently deliver the therapeutic gene, achieved VEGF release to the extracellular medium, and promoted angiogenesis in mouse brain.…”
Section: B Nanotechnology Platformsmentioning
confidence: 99%
“…Also, viral delivery of PlGF (Gaal et al, 2013) and hbFGF (Watanabe et al, 2004), after MCAO, has been performed with AAV and AV, respectively. 2) Non-viral Vegf delivery into the cerebral cortex has been conducted by employing niosomes (Gallego et al, 2020), which enhanced angiogenesis by 55% in normal adult mouse brain, not only at the injection point but also in the vicinity. 3) Epigenetic regulation to achieve an angiogenic response has been developed employing lentiviral-mediated overexpression of miRs injected into the desired area in normal adult mouse brain, with miR-210 (Zeng L et al, 2014), in stroke animal models, with miR-126 (Qu et al, 2019) or miR-210 (Zeng LL et al, 2016), and in AD animal models, with miR-124 (Li et al, 2019a).…”
Section: B Intracerebral Administrationmentioning
confidence: 99%